Investigation of zinc nanoparticles in soil environments - Draper, Rebecca (2021)
Nanoparticles (NPs) are materials that have at least one dimension between 1 – 100 nm. Zinc oxide (ZnO) NPs have properties such as UV-light absorption that make them suitable for adding to personal care products. Many ZnO NP-containing products are routinely rinsed into household wastewater and the resulting zinc NP-containing biosolids frequently used to fertilise agricultural soils.